Relationship between hair nicotine levels with blood pressure, body composition, lipid profile and leptin among healthy male smokers in Kelantan - Harmy, Mohamed Yusoff; Zulkefli, Sanip; Muhammad Zulhusni, Suhaimi (Elsevier B.V., 2016)
Objectives: Cigarette smoking has been reported to cause acute blood pressure elevation. Therefore, it is important to assess the relationships between chronic smoking and blood pressure, body composition, and the metabolic profile to gain an understanding of the long-term effects of smoking on an individual's body weight and health. This study examined the relationships between the hair nicotine level, blood pressure, body composition, lipid profile, and leptin in healthy male smokers.